Balthasar Hacquet and veterinary medicine - Jurca, Jože (Hacquetia, 2015)
Analyses were made for four treatises of veterinary contents, published in 1776 - 1779 by B. Hacquet in Sammlungen Nutzlicher Unterrichte issued by the Society for Agriculture and Useful Crafts of Carniola, and his knowledge and acientific orientation in veterinary medicine were evaluated.